PBAT / bamboo powder compatibility and cross-linking integrated additive, preparation method and application
By using PBAT/bamboo powder compatibility and crosslinking integrated additives in PBAT/bamboo powder composites, a hydrogen bond and chemical bond crosslinking network was constructed, which solved the problem of poor compatibility between PBAT and bamboo powder interface, significantly improved the mechanical properties of the composite materials, and achieved process simplification and cost reduction.
Patent Information
- Application Number
- CN202510078393.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The poor interface compatibility between PBAT and bamboo powder leads to a decline in the mechanical properties of composite materials. The existing modification methods have problems such as complex process, high cost and short-lasting compatibility.
Using PBAT/bamboo powder compatibility and crosslinking integrated additives, the interface compatibility and mechanical properties between PBAT and bamboo powder are improved by building hydrogen bond and chemical bond crosslinking networks. The additive consists of mucic acid, allyl glycidyl ether, nitrilotriacetic acid, etc., and is prepared through specific process steps to form a graft additive precursor and blended with PBAT to improve the mechanical properties of the composite material.
The compatibility between PBAT and bamboo powder and the mechanical properties of the composite material are significantly improved, the preparation cost is reduced, the process is simplified, and the additive itself is biodegradable.
Smart Images

Figure CN119505212B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PBAT modification, and in particular to a PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent, a preparation method and an application thereof. Background Art
[0002] Polybutylene adipate / terephthalate (PBAT), as a fully biodegradable aliphatic-aromatic copolyester, has attracted much attention due to its good processing properties, mechanical properties and biocompatibility. In many fields, especially in the packaging, agricultural mulch and dust net industries in the fields of agriculture and industrial production, PBAT has shown considerable application prospects. However, PBAT still has defects such as low bending strength, low elastic modulus and high cost. Therefore, the research and development of biodegradable composite materials with excellent performance and moderate cost has become one of the hot issues in the current research on PBAT. In terms of reducing the cost of PBAT products, constructing a composite system by PBAT and other environmentally friendly fillers is an effective method.
[0003] As a typical representative of natural agricultural and forestry biomass resources, bamboo powder has the advantages of wide sources, renewable and degradable, and is a highly potential alternative resource for synthetic polymer materials. However, for the PBAT matrix, the compatibility and dispersibility of ordinary bamboo powder are poor. Adding bamboo powder directly to PBAT will significantly weaken the mechanical properties of the composite material. Therefore, it is necessary to increase the capacity and cross-link the PBAT / bamboo powder system.
[0004] At present, the main methods for the compatibilization and cross-linking modification of PBAT and bamboo powder include hydrophobic modification of bamboo powder, and compatibilization and cross-linking modification of PBAT / bamboo powder system by adding compatibilizer and cross-linking agent. For example, NaOH solution and methyltrimethoxysilane are used to synergistically modify bamboo powder. The crystallinity of bamboo powder treated with NaOH solution increases. After further modification by methyltrimethoxysilane, low surface energy Si-CH 3 Groups are added to change the bamboo powder from hydrophilic to hydrophobic, thereby improving the compatibility between bamboo powder and PBAT. However, the alkali treatment modification process is cumbersome and complicated, which is not conducive to the continuity of the production process, and will also produce problems such as "three wastes". For example, the reaction between the polyepoxy functional groups in epoxidized soybean oil and the hydroxyl and carboxyl groups can effectively improve the compatibility and poor dispersibility between PBAT and bamboo powder. However, this type of compatibilizer has the disadvantages of large addition amount, easy migration, and easy adhesion to the machine surface, which leads to the problem that the compatibility between PBAT and bamboo powder cannot be sustained, and then the mechanical properties are reduced. Therefore, it is urgent to develop an auxiliary agent that can improve the interfacial compatibility between PBAT and bamboo powder and improve the mechanical properties of PBAT / bamboo powder composites. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent, a preparation method and an application. The auxiliary agent is green and environmentally friendly, and improves the interface compatibility between PBAT and bamboo powder and the mechanical properties of PBAT / bamboo powder by constructing a hydrogen bond and a chemical bond cross-linking network.
[0006] The present invention proposes a method for preparing a PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent, and the method steps are as follows:
[0007] S1: dissolving mucic acid and zinc acetylacetonate in water in sequence to obtain solution A;
[0008] S2: adding allyl glycidyl ether to solution A to react to obtain solution B;
[0009] S3: adding nitrilotriacetic acid to solution B to continue the reaction to obtain a grafting aid precursor;
[0010] S4: PBAT, initiator and grafting agent precursor are mixed and melt-extruded to obtain PBAT / bamboo powder compatible and cross-linking integrated agent PBAT-g-AGEMUANTA.
[0011] Preferably, the mass ratio of mucic acid, allyl glycidyl ether, zinc acetylacetonate and nitrilotriacetic acid is 1:1-1.5:0.05-0.07:2-3.
[0012] Preferably, the reaction conditions in S2 are: temperature 45-60° C., time 12-16 h.
[0013] Preferably, the reaction conditions in S3 are: temperature 75-90° C., time 4-6 h.
[0014] Preferably, the mass ratio of PBAT, initiator and grafting aid precursor is 10:0.01-0.2:0.05-1.
[0015] Preferably, the conditions for melt extrusion in S4 are: screw speed of 100-200 rpm, feeding rate of 3-6 Hz, and extrusion temperature zones are set to 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C.
[0016] The PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent proposed by the present invention is prepared by the above method.
[0017] The present invention proposes the use of the above-mentioned PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent in PBAT / bamboo powder modified materials.
[0018] Preferably, the method steps are as follows: PBAT, bamboo powder and PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent are mixed at high speed and then melt-extruded.
[0019] Preferably, the mass ratio of PBAT, bamboo powder and PBAT / bamboo powder compatibility and cross-linking integrated additive is 70-80:20-30:0.5-1.5; the conditions for melt extrusion are: screw speed is 200-300rpm, feeding rate is 3-6Hz, and extrusion temperature zone is set to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120℃.
[0020] Beneficial technical effects of the present invention:
[0021] The present invention establishes a quaternary system with PBAT as the grafting main chain, and mucic acid, allyl glycidyl ether, and nitrilotriacetic acid as grafting monomers. The prepared grafting auxiliary agent can be directly added to the PBAT / bamboo powder system, with a small amount of addition, a simple modification process, migration resistance, and complete biodegradability.
[0022] The PBAT-g-AGEMUANTA prepared by the present invention improves the compatibility between PBAT and bamboo powder and the mechanical properties of the PBAT / bamboo powder composite material by constructing a hydrogen bond and a chemical bond cross-linking network. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 FTIR comparison chart of AGEMUANTA-2, PBAT and PBAT-g-AGEMUANTA-2 proposed in the present invention;
[0024] Figure 2 It is the synthesis mechanism diagram of PBAT-g-AGEMUANTA proposed in the present invention;
[0025] Figure 3 It is a diagram of the compatibility and cross-linking mechanism of PBAT / bamboo powder / PBAT-g-AGEMUANTA proposed in the present invention. DETAILED DESCRIPTION
[0026] The present invention will be further explained below in conjunction with specific embodiments.
[0027] The bamboo powder (600-1000 mesh), polybutylene adipate / terephthalate (PBAT), allyl glycidyl ether (AGE), mucic acid (MUA), nitrilotriacetic acid (NTA), zinc acetylacetonate, etc. in the embodiments of the present invention are all commercially available.
[0028] Example 1
[0029] Weigh 3 g of mucic acid, 0.18 g of zinc acetylacetonate and 750 g of distilled water in sequence, first add mucic acid and zinc acetylacetonate into distilled water, stir until dissolved, and then transfer to a three-necked flask to obtain solution A; weigh 3 g of allyl glycidyl ether, use a rubber-tipped dropper to draw allyl glycidyl ether and add it dropwise to solution A at a rate of 1 drop / second, stir and react at 50°C for 16 hours to obtain solution B; weigh 8.19 g of nitrilotriacetic acid, add it to solution B, stir and react at 80°C for 5 hours to obtain solution C.
[0030] Solution C was cooled and transferred to a single-necked flask, and rotary evaporated at 110°C. After rotary evaporation until no liquid dripped out, the remaining portion in the single-necked flask was taken out and dried in an oven at 100°C for 4 h. The dried solid was washed with anhydrous ethanol for more than three times. After washing, the obtained solid was dried in an oven at 100°C for 4 h to obtain a grafting aid precursor, which was recorded as AGEMUANTA-1.
[0031] Weigh 100g PBAT, 2g diisopropylbenzene peroxide and 10g grafting agent precursor AGEMUANTA-1, add them into a high mixer, mix at 200rpm for 10min to obtain a solid mixture; add 112g of the solid mixture into a twin-screw extruder, set the screw speed to 100rpm, the feeding rate to 3Hz, the extrusion temperature zone to 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C, melt-extrude, cool, and dry at 80°C for 12h to obtain a compatible, cross-linked integrated additive, recorded as PBAT-g-AGEMUANTA-1.
[0032] 0.8 kg PBAT, 0.2 kg bamboo powder and 10 g PBAT-g-AGEMUANTA-1 were weighed and mixed at high speed to obtain a mixture; the mixture was melt-extruded, the screw speed was set to 200 rpm, the feeding rate was 4 Hz, and the extrusion temperature zones were set to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120 ° C to obtain PBAT / bamboo powder modified material-1.
[0033] Example 2
[0034] Weigh 3 g of mucic acid, 0.18 g of zinc acetylacetonate and 750 g of distilled water in sequence, first add mucic acid and zinc acetylacetonate into distilled water and stir until dissolved, then transfer to a three-necked flask to obtain solution A; S2: weigh 3.75 g of allyl glycidyl ether, use a rubber-tipped dropper to draw allyl glycidyl ether and add it dropwise to solution A at a rate of 1 drop / second, stir and react at 50°C for 16 hours to obtain solution B; S3: weigh 8.19 g of nitrilotriacetic acid and add it to solution C, stir and react at 80°C for 5 hours to obtain solution C.
[0035] Solution C was cooled and transferred to a single-necked flask, and rotary evaporated at 110°C. After rotary evaporation until no liquid dripped out, the remaining portion in the single-necked flask was taken out and dried in an oven at 100°C for 4 h. The dried solid was washed with anhydrous ethanol for more than three times. After washing, the obtained solid was dried in an oven at 100°C for 4 h to obtain a grafting aid precursor, which was recorded as AGEMUANTA-2.
[0036] Weigh 100g PBAT, 2g dicumyl peroxide and 10g grafting agent precursor AGEMUANTA-2 into a high mixer, mix at 200rpm for 10min to obtain a solid mixture; add 112g of the solid mixture into a twin-screw extruder, set the screw speed to 100rpm, the feeding rate to 3Hz, the extrusion temperature zone to 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C, melt-extrude, cool, and dry at 80°C for 12h to obtain a compatible, cross-linked integrated additive, recorded as PBAT-g-AGEMUANTA-2;
[0037] Weigh 0.8 kg PBAT, 0.2 kg bamboo powder and 10 g PBAT-g-AGEMUANTA-2, and mix them at high speed to obtain a mixture; melt-extrude the mixture, set the screw speed to 200 rpm, the feeding rate to 4 Hz, and the extrusion temperature zone to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120 ° C to obtain PBAT / bamboo powder modified material-2.
[0038] Example 3
[0039] Weigh 3 g of mucic acid, 0.18 g of zinc acetylacetonate and 750 g of distilled water in sequence, first add mucic acid and zinc acetylacetonate into distilled water, stir until dissolved, and then transfer to a three-necked flask to obtain solution A; weigh 4.50 g of allyl glycidyl ether, use a rubber-tipped dropper to draw allyl glycidyl ether and add it dropwise to solution A at a rate of 1 drop / second, stir and react at 50°C for 16 hours to obtain solution B; weigh 8.19 g of nitrilotriacetic acid, add it to solution B, stir and react at 80°C for 5 hours to obtain solution C.
[0040] Solution C was cooled and transferred to a single-necked flask, and rotary evaporated at 110°C. After rotary evaporation until no liquid dripped out, the remaining portion in the single-necked flask was taken out and dried in an oven at 100°C for 4 h. The dried solid was washed with anhydrous ethanol for more than three times. After washing, the obtained solid was dried in an oven at 100°C for 4 h to obtain a grafting aid precursor, which was recorded as AGEMUANTA-3.
[0041] Weigh 100g PBAT, 2g diisopropylbenzene peroxide and 10g grafting agent precursor AGEMUANTA-3 into a high mixer, mix at 200rpm for 10min to obtain a solid mixture; add 112g of the solid mixture into a twin-screw extruder, set the screw speed to 100rpm, the feeding rate to 3Hz, the extrusion temperature zone to 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C, melt-extrude, cool, and dry at 80°C for 12h to obtain a compatible, cross-linked integrated additive, recorded as PBAT-g-AGEMUANTA-3.
[0042] Weigh 0.8 kg PBAT, 0.2 kg bamboo powder and 10 g PBAT-g-AGEMUANTA-3, mix them at high speed to obtain a mixture; melt-extrude the mixture, set the screw speed to 200 rpm, the feeding rate to 4 Hz, and the extrusion temperature zone to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120 ° C to obtain PBAT / bamboo powder modified material-3.
[0043] Comparative Example 1
[0044] Weigh 0.8 kg PBAT and 0.2 kg bamboo powder, mix them at high speed to obtain a mixture; melt-extrude the mixture, set the screw speed to 200 rpm, the feeding rate to 4 Hz, and the extrusion temperature zone to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120 ° C to obtain PBAT / bamboo powder modified material-4.
[0045] Comparative Example 2
[0046] Weigh 3 g of mucic acid, 0.18 g of zinc acetylacetonate and 750 g of distilled water in sequence, first add mucic acid and zinc acetylacetonate into distilled water, stir until dissolved, and then transfer to a three-necked flask to obtain solution A; weigh 2 g of allyl glycidyl ether, use a rubber-tipped dropper to draw allyl glycidyl ether and add it dropwise to solution A at a rate of 1 drop / second, stir and react at 50°C for 16 hours to obtain solution B; weigh 8.19 g of nitrilotriacetic acid, add it to solution B, stir and react at 80°C for 5 hours to obtain solution C.
[0047] Solution C was cooled and transferred to a single-necked flask, and rotary evaporated at 110°C. After rotary evaporation until no liquid dripped out, the remaining portion in the single-necked flask was taken out and dried in an oven at 100°C for 4 hours. The dried solid was washed with anhydrous ethanol for more than three times. After washing, the obtained solid was dried in an oven at 100°C for 4 hours to obtain a grafting aid precursor, which was recorded as AGEMUANTA-5.
[0048] Weigh 100g PBAT, 2g diisopropylbenzene peroxide and 10g grafting agent precursor AGEMUANTA-5, add them into a high mixer, mix at 200rpm for 10min to obtain a solid mixture; add 112g of the solid mixture into a twin-screw extruder, set the screw speed to 100rpm, the feeding rate to 3Hz, the extrusion temperature zone to 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C, melt-extrude, cool, and dry at 80°C for 12h to obtain a compatible, cross-linked integrated additive, recorded as PBAT-g-AGEMUANTA-5.
[0049] Weigh 0.8 kg PBAT, 0.2 kg bamboo powder and 10 g PBAT-g-AGEMUANTA-5, and mix them at high speed to obtain a mixture; melt-extrude the mixture, set the screw speed to 200 rpm, the feeding rate to 4 Hz, and the extrusion temperature zone to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120 ° C to obtain PBAT / bamboo powder modified material-5.
[0050] Comparative Example 3
[0051] Weigh 3 g of mucic acid, 0.18 g of zinc acetylacetonate and 750 g of distilled water in sequence, first add mucic acid and zinc acetylacetonate into distilled water, stir until dissolved, and then transfer to a three-necked flask to obtain solution A; weigh 5 g of allyl glycidyl ether, use a rubber-tipped dropper to draw allyl glycidyl ether and add it dropwise to solution A at a rate of 1 drop / second, stir and react at 50°C for 16 hours to obtain solution B; weigh 8.19 g of nitrilotriacetic acid, add it to solution B, stir and react at 80°C for 5 hours to obtain solution C.
[0052] Solution C was cooled and transferred to a single-necked flask, and rotary evaporated at 110°C. After rotary evaporation until no liquid dripped out, the remaining portion in the single-necked flask was taken out and dried in an oven at 100°C for 4 h. The dried solid was washed with anhydrous ethanol for more than three times. After washing, the obtained solid was dried in an oven at 100°C for 4 h to obtain a grafting aid precursor, which was recorded as AGEMUANTA-6.
[0053] Weigh 100g PBAT, 2g dicumyl peroxide and 10g grafting agent precursor AGEMUANTA-6 into a high mixer, mix at 200rpm for 10min to obtain a solid mixture; add 112g of the solid mixture into a twin-screw extruder, set the screw speed to 100rpm, the feeding rate to 3Hz, the extrusion temperature zone to 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C, melt-extrude, cool, and dry at 80°C for 12h to obtain a compatible, cross-linked integrated additive, recorded as PBAT-g-AGEMUANTA-6.
[0054] Weigh 0.8 kg PBAT, 0.2 kg bamboo powder and 10 g PBAT-g-AGEMUANTA-6, and mix them at high speed to obtain a mixture; melt-extrude the mixture, set the screw speed to 200 rpm, the feeding rate to 4 Hz, and the extrusion temperature zone to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120 ° C to obtain PBAT / bamboo powder modified material-6.
[0055] The present invention performs infrared tests on PBAT, AGEMUANTA-2 and PBAT-g-AGEMUANTA-2, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that in the infrared spectrum of the synthesized grafting auxiliary precursor AGEMUANTA-2, the -1 The absorption peak at 1080cm -1 The absorption peak at 1130 cm-1 The absorption peak at is the stretching vibration peak of COC in the ester group. It can be seen that AGE, MUA and NTA have been successfully reacted.
[0056] At the same time, compared with the infrared spectrum of pure PBAT, the spectrum of PBAT-g-AGEMUANTA-2 shows the following significant features: -1 The absorption peak at 1640cm is the stretching vibration peak of OH; -1 The peak at 1130 cm is the stretching vibration peak of C=C; in particular, -1 The peak intensity of the stretching vibration peak of COC in the ester group increases; at 1080cm -1 The peak at 3056cm is the stretching vibration peak of CN in the tertiary amine group; -1 The peak at 720cm is the stretching vibration peak of =CH; -1 The peak at 720 cm is the in-plane swing vibration of the methylene group in the straight-chain alkane, and it can be seen that -1 The peak intensity of the peak at 40° is reduced. Based on the changes in the above spectral characteristics, it can be seen that AGEMUANTA-2 has been successfully grafted onto PBAT.
[0057] The present invention conducts mechanical property tests on PBAT, modified materials of Examples 1-3 and Comparative Examples 1-3, and the results are shown in Table 1.
[0058] As shown in Table 1, the pure PBAT film sample has the best mechanical properties, and the mechanical properties are greatly reduced after filling with bamboo powder. In the sample filled with bamboo powder, when the mass ratio of allyl glycidyl ether to mucic acid is 1.25:1, the tensile strength of the film sample is the best, and the longitudinal tensile strength can reach 22.97Mpa; the transverse tensile strength can reach 18.65Mpa. The reason for the above phenomenon is that when PBAT is directly blended with bamboo powder, due to the poor interfacial compatibility between PBAT and bamboo powder, stress concentration and cracking occur in the film during the stretching process, so the mechanical properties are greatly reduced. However, after adding PBAT-g-AGEMUANTA, the tensile strength of the film is significantly improved. The reason is that PBAT-g-AGEMUANTA enhances the intermolecular forces in the PBAT / bamboo powder system by constructing a hydrogen bond and chemical bond cross-linking network, thereby improving the compatibility between PBAT and bamboo powder and the tensile strength of the PBAT / bamboo powder system. Further analysis shows that when the proportion of allyl glycidyl ether is low, the double bond content of the grafting agent precursor is low, resulting in a low grafting rate between the grafting agent precursor and PBAT. When the proportion of allyl glycidyl ether is high, allyl glycidyl ether will occupy the reaction sites of nitrilotriacetic acid, thereby reducing the content of carboxyl groups used for cross-linking in the grafting agent. The above reasons will reduce the compatibilization and cross-linking effects of the synthesized grafting agent, thereby reducing the mechanical properties of the film.
[0059] Table 1 Mechanical properties test
[0060]
Claims
1. A method for preparing a PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent, characterized in that: The steps are as follows: S1: dissolving mucic acid and zinc acetylacetonate in water in sequence to obtain solution A; S2: adding allyl glycidyl ether to solution A to react to obtain solution B; S3: adding nitrilotriacetic acid to solution B and continuing the reaction to obtain a grafting aid precursor; S4: mixing poly(butylene adipate / terephthalate), an initiator and a grafting agent precursor and then melt-extruding them to obtain a compatible and cross-linking integrated agent; The mass ratio of mucic acid, allyl glycidyl ether, zinc acetylacetonate and nitrilotriacetic acid is 1:1-1.5:0.05-0.07:2-3.
2. The method for preparing the PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent according to claim 1, characterized in that: The reaction conditions in S2 are: temperature 45-60°C, time 12-16h.
3. The method for preparing the PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent according to claim 1, characterized in that: The reaction conditions in S3 are: temperature 75-90°C, time 4-6h.
4. The method for preparing the PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent according to claim 1, characterized in that: The mass ratio of poly(adipate) / butylene terephthalate, initiator and grafting auxiliary agent precursor is 10:0.01-0.2:0.05-1.
5. The method for preparing the PBAT / bamboo powder compatibility and cross-linking integrated auxiliary agent according to claim 1, characterized in that: The conditions for melt extrusion in S4 are: screw speed of 100-200 rpm, feeding rate of 3-6 Hz, and extrusion temperature zones of 170, 170, 175, 175, 175, 175, 180, 180, 180, 175, 175, 170°C.
6. A compatibilizing and cross-linking integrated auxiliary agent, characterized in that: The method is prepared by any one of claims 1 to 5.
7. Use of the integrated compatibility and cross-linking auxiliary agent as claimed in claim 6 in poly(butylene adipate) / terephthalate modified materials.
8. A method for preparing a poly(butylene adipate) / terephthalate modified material, characterized in that: The method comprises the following steps: mixing poly(butylene adipate / terephthalate), bamboo powder and the compatible and cross-linking integrated auxiliary agent as claimed in claim 6 at a high speed and then performing melt extrusion.
9. The method for preparing the poly(butylene adipate / terephthalate) modified material according to claim 8, characterized in that: The mass ratio of polybutylene adipate / terephthalate, bamboo powder, and compatible and cross-linking integrated additives is 70-80:20-30:0.5-1.5; the conditions for melt extrusion are: screw speed is 200-300rpm, feeding rate is 3-6Hz, and extrusion temperature zones are set to 120, 120, 125, 125, 125, 125, 130, 130, 130, 125, 125, 120℃.
Citation Information
Patent Citations
Solid polymer composition obtained by polymerization of an acid group-containing monomer in the presence of a polyether compound
CN105518038A
Compatibility and nucleation integrated auxiliary agent of PBAT / cellulose as well as preparation method and application of compatibility and nucleation integrated auxiliary agent
CN118005905A
Cited By
Preparation method of high-compatibility PBAT bamboo powder composite master batch
CN122011438A